Теоретичне дослідження процесу розгону колісного трактора з безступінчастою гідрооб'ємно-механічною трансмісією при оранці - Кожушко, Андрій Павлович; Агапов, Олег Миколайович (НТУ "ХПІ", 2017)
В роботі наведено підхід для формування раціональної зміни параметрів регулювання гідромашин гідрооб’ємної передачі для колісних тракторів, що оснащені безступінчастою гідрооб’ємно-механічною трансмісією, в умовах виконання технологічної операції оранка. Проведено теоретичне дослідження процесу розгону колісного трактора, в складі машинно-тракторного агрегату, при виконанні операції оранка. Виконано порівняльний аналіз застосування лінійної та раціональної зміни параметрів регулювання гідромашин гідрооб’ємної передачі та, відповідно, визначено зміну таких показників машинно-тракторного агрегату, як витрати палива та продуктивності.

The paper forming a rational approach for changing the parameters of regulation of hydraulic transmission hydraulic machines for wheel tractors that are equipped with continuously variable hydrovolumetric manual transmission, in terms of implementation of technological operations plowing. Based on the analysis of recent research and kinematic calculation, power and energy performance of selected two promising hydrovolumetric mechanical transmission with differential circuits with input and differential output. A theoretical study of the process of acceleration wheeled tractor composed tractor unit, when executing plowing. A comparative analysis of the linear and in the course of optimization of parameters of rational regulation of hydraulic transmission hydraulic machines. On the basis of comparative analysis the changing technical and economic indicators tractor unit, namely, fuel consumption and performance.
Theoretical investigation of the acceleration wheeled tractor with continuously variable transmission for plowing
Keywords: техніко-економічні показники; гідрооб'ємна передача; двигуни внутрішнього згоряння; машинно-тракторні агрегати; tractor; acceleration; continuously variable transmission; technical and economic indicators; hydraulic transmission